Assessment of Stress and Burnout among Postgraduate Medical Students - N Chandan; Mayur S Sherkhane (Medsci Publications, 2017)
Introduction: Medical education and healthcare are inherently stressful and demanding. Optimal level of stress enhances learning while excess of stress can lead to health problems. If untreated can lead to multiple disorders like sleeping disturbances, insomnia and further may lead to burnout. Objectives: To assess the level of stress among postgraduates and to know risk factors leading to burnout. Methodology: Cross sectional study was conducted among 120 postgraduates in a medical college. Data was collected using pre-designed questionnaire. Perceived stress scale-14 was used to assess stress and Maslach Burnout Inventory was used to assess burnout. Results: Mean age of the study participants was 27.39±2.84 years. 53.33% were males and 46.67% females. Prevalence of stress was 91.67%. Among them, 37.50% had mild stress and 22.50% had severe stress. Prevalence of burnout was 45.0%. Stress levels were higher among 93.75% males, 94.73% second year, 92.11% clinical postgraduates and all married postgraduates (p>0.05). Burnout was significantly more among third year postgraduates compared to others (p=0.016). 51.56% males, 54.55% clinical and 60.71% married postgraduates had burnout (p>0.05). Conclusions: PSS-14 and MBI-SS can be used as screening tools for early diagnosis and preventive measures like counselling can be initiated at the earliest to all.